Dengue Underestimation in Guangzhou, China: Evidence of Seroprevalence in Communities With No Reported Cases Before a Large Outbreak in 2014. (3rd June 2019) - Jing, Qinlong; Li, Yilan; Liu, Jianhua; Jiang, Liyun; Chen, Zongqiu; Su, Wenzhe; Birkhead, Guthrie S; Lu, Jiahai; Yang, Zhicong
Abstract: Objective: Dengue has become a serious public health problem in southern China particularly with a record-breaking outbreak in 2014. Serological evidence from areas with no known dengue cases reported prior to 2014 could provide information on possible unrecognized circulation of dengue virus (DENV) before this outbreak. Method: Between March and May 2015, we performed a cross-sectional serosurvey using a stratified random sampling method among individuals aged 1–84 years-old in 7 communities in Guangzhou with no reported dengue cases before 2014. Sera of subjects were initially screened with the indirect DENV IgG enzyme-linked immunosorbent assay, and positive samples were further tested by the indirect immunofluorescence assay to identify specific serotypes. Results: A total of 850 subjects had complete information available. The overall seroprevalence against DENV was 6.59% (56 of 850; 95% CI, 4.92%–8.26%). The seroprevalence increased with age in general (3.86%, 4.58%, 8.72%, 7.22%, and 10.69% among participants in ≤14, 15–29, 30–44, 45–59 and ≥60 years age group, respectively). Living in rural or peri-urban communities and longer years of residence therein were risk factors for higher seroprevalence, whereas wearing long sleeves and pants when outdoors was associated with lower seroprevalence. Of the total subjects, 55.36% (31 of 56) sera were successfully identified with specific serotypes, with 12.90% (4 of 31) being coinfected with 2 serotypes. Conclusions: Dengue transmission in the study communities had occurred prior to the 2014 massive outbreak, possibly for many years, but went undiagnosed and unreported. A proportion of the study population experienced secondary infection as different serotypes of DENV increased the risk for severe diseases. Active surveillance and education of both healthcare providers and the general population should be conducted in areas at risk for dengue emergence in order to better reduce disease burden. Abstract : The 2015 cross-sectional, stratified random sampling serosurvey in areas with no reported cases before the large outbreak in 2014 in Guangzhou indicated dengue transmission occurred prior to the 2014 for many years, but went undiagnosed and unreported.